1951
DOI: 10.1172/jci102433
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Protein Consumption and Diurnal Variations of the Endogenous Creatinine Clearance in Normal Individuals 1

Abstract: In a previous paper based on the same study (1), it was shown that the serum urea concentration of subjects with intact renal function increases with protein consumption. In contrast, the serum creatinine concentration in such subjects was shown to be independent of protein consumption (2). It has long been known that endogenous urea excretion increases with the protein consumed, while the rate of endogenous creatinine excretion has been shown to be relatively independent of the amount of protein consumed (3).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1952
1952
1989
1989

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…The administration of renin resulted in a tremendous increase in protein excretion in the rat (2). All of the serum proteins appear to be excreted, with the possible exception of a2-globulin, z Thus, electrophoretic patterns of urinary proteins following renin administration differed strikingly from those of normal urinary proteins, but bore a close resemblance to normal serum protein patterns (Fig.…”
Section: The Influence Of Renin On Urinary Excretion Of Proteins--thmentioning
confidence: 83%
See 1 more Smart Citation
“…The administration of renin resulted in a tremendous increase in protein excretion in the rat (2). All of the serum proteins appear to be excreted, with the possible exception of a2-globulin, z Thus, electrophoretic patterns of urinary proteins following renin administration differed strikingly from those of normal urinary proteins, but bore a close resemblance to normal serum protein patterns (Fig.…”
Section: The Influence Of Renin On Urinary Excretion Of Proteins--thmentioning
confidence: 83%
“…Following renin administration, a massive proteinuria occurs (2). The proteins excreted are similar in electric mobility and relative distribution to those of normal rat serum, although "albumin" is present in a higher relative concentration in urine than in serum and has a somewhat greater mobility.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast to the measured CCr, which suffers from these variations, prediction methods by definition are not influenced because in these methods serum creatinine (SCr) is the only variable parameter for a given individual. The diurnal variation of SCr has been reported to be only 10-15% in an individual (Addis et al, 1950;Doolan et al, 1962;Statland et al, 1973;Winkel et al, 1975), while the urinary creatinine excretion can vary between 30 and 400% (Clark et al, 1951;Pasternack & Kuhlback, 1971;Greenblatt et al, 1976;Maruhn et al, 1977). Because of these large variations in urinary creatinine excretion, measured CCr will vary accordingly.…”
Section: Creatinine Clearance Different Methods Of Determinationmentioning
confidence: 98%
“…A description of the methods used in the collection and analysis of the urine is given in a previous paper (1). Young female rats of about 150 gm.…”
Section: Methodsmentioning
confidence: 99%
“…(Received for publication, February 15, 1950) In a previous paper (1) it was suggested that the pmteinuria which occurs in the rat following the intraperitoneal injection of renin was due to constriction of the efferent glomerular arteriole, a consequent increase in the intraglomerular filtration pressure, and the passage of more protein through the glomerular membrane. It was shown that inactivation of renin with respect to its pressor activity led, under the conditions of the experiments, to a loss of its capacity to induce proteinuria.…”
mentioning
confidence: 99%